Household debt in Sweden an empirical investigation of the determinants of the debt increase from 1980-2009 - Panic,Sanja (2010)
The Swedish household debt has been quite high and increasing for the past 30 years. In this thesis I tried to find the underlying reasons for the development in the long-run by using the Engle-Granger two-step model for co-integration but found that there was no co-integration between the household debt to disposable income ratio and the chosen variables. In the short-run analysis I de-trended all the variables and proceeded with an OLS regression and found that the debt to disposable income ratio was determined by all the variables but especially by debt to assets, the demographic variable and the real estate prices.
Keywords: Household debt; Sweden; Engle-Granger; Life-cycle hypothesis; co-integration